The Availability of Strategic Planning Indicators from Students Points of Views at Irbid Private University in Jordon - Wafa Al-Ashqar (University of Science and Technology, Yemen, 2014)
Abstract: Degree of awareness of students at National University of Irbed with the indicators for university strategic planning The study aimed to evaluate the degree of awareness of students at Irbed National University with the various indicators for strategic planning. To achieve this، a questionnaire was adopted to deal with 2 main topics، first evaluation of the degree of awareness of the students with various indicators of strategic planning: goals، mission، vision and values. The second topic is to assess any degree of correlation between the awareness of the students to these fields and variables related to sex، type of faculty، and academic year. The study showed that awareness of the students to these fields is within average values، and there is no statistically significant differences between the degree of awareness of the students attributed to  these  variables. Accordingly the author advises to increase the students awareness to these fields by stressing on programmers that explain the role of the university in community and services offered to students and to intensify values of faith and fidelity to university and to construct programmers that create students with knowledge and technology.   Keywords: strategic planning، vision، mission، values، strategic goals، high education